Survival Analysis of Chronic Kidney Disease Patients with Hemodialysis in West Java. Indonesia, Year 2007 - 2018 - Afiatin Afiatin; Dwi Agustian; Kurnia Wahyudi; Pandu Riono; Rully M. A. Roesli (Majalah Kedokteran Bandung, 2020)
The prevalence of chronic kidney disease on dialysis or CKD5D is increasing with a significant impact on disease burden in many countries. Patients are usually listed in the national renal registries, which report demographic data, incidence, prevalence, and outcome. The survival rate is an important outcome measure to characterize the impact of treatment in the CKD5 patient population in the national and international renal registries. Indonesian Society of Nephrology (InaSN) has the Indonesian Renal Registry program to collect data that was endorsed to monitor dialysis treatment quality in Indonesia.  IRR releases an annual report, but there is no survival analysis yet.   This study aimed to discover the five-year survival rate of CKD5D patients in West Java between 2007–2018 and its factor based on the IRR database. A retrospective cohort study was performed by gaining all patients' data from the IRR database, then data on all of the patients from West Java province who completed a 5-year follow-up on December 31, 2018.  Kaplan-Meier analysis and Cox proportional hazard's model were used to analyze the risk factors. There were 3,199 data included in this study. In total, the 1, 2, 3, 4, and 5 year survival rates are 82%, 70%, 62%, 58%, and 55 %, respectively.  Patients whose age is above 55 years and with unknown underlying kidney disease have a worse survival rate with a hazard ratio of 1.28 and 1.50, respectively. Further exploration of IRR data will provide better information on dialysis treatment in Indonesia. Ketahanan Hidup Pasien Penyakit Ginjal Kronis dengan Hemodialisis di Jawa Barat Indonesia tahun 2007-2018Prevalensi penyakit ginjal kronis pada dialisis atau PGK5D meningkat dan memberi beban penanganan penyakit di banyak negara. Pasien biasanya terdaftar dalam register ginjal nasional yang melaporkan data demografis, insiden, prevalensi dan luaran klisis. Tingkat ketahanan hidup merupakan parameter penting dalam registrasi ginjal untuk menggambarkan kualitas terapi pada  populasi pasien PGK stadium 5. Perhimpunan Nefrologi Indonesia (Pernefri) memiliki program Registri Ginjal Indonesia yang disebut Indonesian Renal Registry (IRR) untuk mengumpulkan data pasien PGK5D untuk  memantau kualitas pengobatan dialisis di Indonesia. IRR merilis laporan tahunan tetapi belum dilengkapi dengan  analisis ketahanan hidup. Tujuan penelitian ini adalah mengetahui angka ketahanan hidup lima tahun pasien PGK5D di Jawa Barat antara tahun 2007-2018 dan faktor risikonya berdasarkan basis data dari IRR. Studi kohort retrospektif dengan mengambil semua data pasien dari basis data IRR kemudian ditentukan data pasien Jawa Barat yang lengkap dan di follow up selama 5 tahun pada 31 Desember 2018.   Analisis Kaplan-Meier dan model proporsional hazard Cox digunakan untuk menganalisis faktor risiko. Subjek berjumlah 3199 data yang dimasukkan dalam penelitian ini. Kesimpulannya, angka harapan hidup satu, 2, 3, 4, dan 5 tahun berturut-turut adalah 82%, 70%, 62%, 58%, dan 55%. Usia lebih dari 55 tahun dan penyakit ginjal yang mendasari memiliki kelangsungan hidup yang lebih buruk dengan hazard ratio 1,28 dan 1,50. Eksplorasi lebih lanjut dari data IRR akan memberikan informasi yang lebih baik tentang perawatan dialisis di Indonesia.